Problem Based Learning Experience at the Medical School in King Abdulaziz University: Reasons for Not Participating as Problem Based Learning Facilitators - Mawya A. Khafaji,; Lana A. Al Shawwa, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The Faculty of Medicine at King Abdulaziz University, Jeddah started in 1975, and has been running a traditional curriculum for over 30 years. A few years back, it embarked on changing its curriculum to an integrated system based curriculum. Including different teaching strategies e.g., lectures, problem based learning, practical sessions, clinical teaching, student directed learning, early clinical exposure and communication skills with emphasis on critical thinking, problem solving, case based learning and evidence based practice. The curriculum was implemented in the academic year 2007/2008. The school invested in training staff to become Problem Based Learning tutors and recruited experts to supervise and maintain the new curriculum. A designed questionnaire was sent to the nonparticipating faculty members. Clinicians were found to be the majority of the non participating tutors (91%); and that there was no difference with regards to gender (56% male and 43% female). The Faculty of Medicine in King Abdulaziz University is successfully embarking on curriculum change. They are challenged with staff development and participation.